Front Cover: Proof of Equivalent Catalytic Functionality upon Photon‐Induced and Thermal Activation of Supported Isolated Vanadia Species in Methanol Oxidation (ChemCatChem 11/2018). Issue 11 (7th June 2018) - Kortewille, Bianca; Wachs, Israel E.; Cibura, Niklas; Pfingsten, Oliver; Bacher, Gerd; Muhler, Martin; Strunk, Jennifer
Abstract : The Front Cover shows an isolated, dehydrated vanadium oxide species on a silica support. In their Communication, B. Kortewille et al. demonstrate that such species can perform selective oxidation of methanol to formaldehyde both photon‐induced and by thermal activation. The selectivity to formaldehyde in the photocatalytic process appears to be unity, but product desorption is hindered at room temperature. Supported V2 O5 nanoparticles, on the other hand, are inactive in the photon‐induced process and can carry out the reaction only by thermal activation. The results have important implications for the design of active sites for photocatalysis. More information can be found in the Communication by B. Kortewille et al. onpage 2360 in Issue 11, 2018 (DOI:10.1002/cctc.201800311 ).